Physical Function of RA patients Tapering Treatment—A Post Hoc Analysis of the Randomized Controlled RETRO Trial - Stephan, Marlene; Tascilar, Koray; Yalcin-Mutlu, Melek; Hagen, Melanie; Haschka, Judith; Reiser, Michaela; Hartmann, Fabian; Kleyer, Arnd; Hueber, Axel; Manger, Bernhard; Figueiredo, Camille; Cobra, Jayme Fogagnolo; et al. (Journal of Clinical Medicine, 2023)
Several studies have shown that tapering or stopping disease-modifying anti-rheumatic drugs (DMARDs) in rheumatoid arthritis (RA) patients in sustained remission is feasible. However, tapering/stopping bears the risk of decline in physical function as some patients may relapse and face increased disease activity. Here, we analyzed the impact of tapering or stopping DMARD treatment on the physical function of RA patients. The study was a post hoc analysis of physical functional worsening for 282 patients with RA in sustained remission tapering and stopping DMARD treatment in the prospective randomized RETRO study. HAQ and DAS-28 scores were determined in baseline samples of patients continuing DMARD (arm 1), tapering their dose by 50% (arm 2), or stopping after tapering (arm 3). Patients were followed over 1 year, and HAQ and DAS-28 scores were evaluated every 3 months. The effect of treatment reduction strategy on functional worsening was assessed in a recurrent-event Cox regression model with a study-group (control, taper, and taper/stop) as the predictor. Two-hundred and eighty-two patients were analyzed. In 58 patients, functional worsening was observed. The incidences suggest a higher probability of functional worsening in patients tapering and/or stopping DMARDs, which is likely due to higher relapse rates in these individuals. At the end of the study, however, functional worsening was similar among the groups. Point estimates and survival curves show that the decline in functionality according to HAQ after tapering or discontinuation of DMARDs in RA patients with stable remission is associated with recurrence, but not with an overall functional decline.
CRIS-Team Scopus Importer:2023-06-30
Keywords: DAS28; DMARD; HAQ; PROM’s; Rheumatoid Arthritis